(3GdTQjajI Ydi TQM GdeNJUQ GdYVOjs - (3GdLQLGfj, GdTQja, Ydj Hf eMeO Hf Ydj, J (B816 (3g`s ((3GdbOSs)
(3ChdgG (B:s
... (3bhdg ef dWa Gddg JYGdi jYfj ef dWa Gddg SHMGfg dYHGOg CMOGK GdehVhYGJ GddZhjI aEfg Cj aEf Gddg JYGdi , hGdaGA dJaVjd eG bHdgG Ch ef Mbg Cf jYbH GdELeGd deG Yde MGLI GdfGS Edi JYQja HYVge HYVG hEYdGege (B...s
(3BNQgG (B:s
..(3hbjd dG ajgeG Ydi GdGNJdGa aj GdCSHGH eY GfgG JJab YdjgG hPdc Cf JNU ZjQ GdTQW GdTQYj HeG YOG GdCSHGH hdG jdRe EgeGd MGdgG dGfgG bO YdeJ ggfG hGddg CYde HGdUhGH (B. (3JeJ GdMGTjIs
(3JHUQI GdYfhGf (B:s
(3MGTjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ddRQcdj (B5/7s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdfMhs